A path tracking Algorithm using the IEEE 802.11 Infrastructure - Mezali, Yacine; Jacquet, Philippe; Rodolakis, Georgios (2011 the 10th IFIP Annual Mediterranean Ad Hoc Networking Workshop, 2011)
We propose a new indoor tracking method which can be used on mobile nodes. Our method uses only the received signal strengths as input information and does not require a cinematic motion model to track the mobile node. We discuss in detail the features of our approach and its resulting algorithm. We evaluate the performances of our algorithm using a real signal map.